2015
DOI: 10.17271/1980082711620151255
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação Da Teoria Fuzzy Em Modelos De Transporte De Poluentes Em Rios, Para Estudar Funções De Pertinência Relacionadas Com Campos De Concentração, Em Função Das Características Do Rio

Abstract: RESUMONeste trabalho, desenvolveu-se uma metodologia que combina a teoria fuzzy com os processos de transporte de poluente, para estudar os campos de concentração em rios, do ponto de vista de incertezas. A metodologia emprega fundamentos da teoria fuzzy para avaliar a solução da equação da difusão advectiva e, assim, transformar um campo de concentração, variável no tempo e espaço, em um campo de funções de pertinências, também variáveis no tempo e no espaço. Os resultados permitiram concluir que a aplicação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A detailed review of the basic concepts of fuzzy sets and their integration using GIS can be found in Robinson (2003). The integration of fuzzy logic with GIS in a decision-making structure has been used for different purposes in environmental studies, including geotechnical disaster risk management (Machado et al 2018), landscape analysis (França et al 2014), analysis of environmental degradation in rivers (Lopes et al 2016, Vidal et al 2015, forest planning (Boyland et al 2006, Diaz-Balteiro & Romero, 2008, and more specifically, the modeling of the risk of forest fires ( Güngöroğlu 2017, Mehta et al 2018, Semeraro et al 2016, Sharma et al 2012. Thus, many studies have been carried out using fuzzy logic integrated with GIS, demonstrating that the methods are robust and valid.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of the basic concepts of fuzzy sets and their integration using GIS can be found in Robinson (2003). The integration of fuzzy logic with GIS in a decision-making structure has been used for different purposes in environmental studies, including geotechnical disaster risk management (Machado et al 2018), landscape analysis (França et al 2014), analysis of environmental degradation in rivers (Lopes et al 2016, Vidal et al 2015, forest planning (Boyland et al 2006, Diaz-Balteiro & Romero, 2008, and more specifically, the modeling of the risk of forest fires ( Güngöroğlu 2017, Mehta et al 2018, Semeraro et al 2016, Sharma et al 2012. Thus, many studies have been carried out using fuzzy logic integrated with GIS, demonstrating that the methods are robust and valid.…”
Section: Introductionmentioning
confidence: 99%